Preliminary Comparison of Wet Bypass Accident Consequences Between ITER and a Helium-Cooled Fusion Power Plant. (3rd October 2018) - Chen, Shanqi; Ge, Daochuan; Wang, Zhen; Jia, Jiangtao; Chen, Zhibin; Hu, Liqin
Abstract: No-public evacuation is an expectation for fusion power plants (FPPs) from the public and governments. In this technical note, a preliminary consequence assessment of an ITER wet bypass–like accident (the accident with the most severe consequence in ITER) of a helium-cooled deuterium-tritium tokamak FPP is performed and compared with that of ITER. Ideal gas–based methodology is proposed to evaluate the released materials in accidents, which is verified by typical accident cases in FPPs. The verification indicates that, compared with the best estimated codes, the proposed method is much simpler and easier with effectiveness. The accident assessment shows that this helium-cooled FPP design may still need public evacuation if the accident happens, which demonstrates the requirement of further investigations for FPP accidents. Some suggestions are proposed to improve the safety of FPPs based on the assessment.